Individualized PID tuning for maintenance of general anesthesia with propofol and remifentanil coadministration. (January 2022) - Schiavo, Michele; Padula, Fabrizio; Latronico, Nicola; Paltenghi, Massimiliano; Visioli, Antonio
Abstract: In this paper we propose a methodology for a patient-individualized tuning of the parameters of a proportional–integral–derivative (PID) controller that regulates the depth of hypnosis in the maintenance phase of general anesthesia. In particular, we consider a PID controller employed in a closed-loop multiple-input–single-output (MISO) control system for propofol and remifentanil coadministration. Simulation results show that the approach provides an increased robustness with respect to both intra-patient and inter-patient compared to a population-based tuning. This is obtained at the cost of a slight decrement of the controller bandwidth that causes a minor increment of the time required to reject disturbances.